If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(4x + -5) + 4 = 3x + -21 Reorder the terms: 2(-5 + 4x) + 4 = 3x + -21 (-5 * 2 + 4x * 2) + 4 = 3x + -21 (-10 + 8x) + 4 = 3x + -21 Reorder the terms: -10 + 4 + 8x = 3x + -21 Combine like terms: -10 + 4 = -6 -6 + 8x = 3x + -21 Reorder the terms: -6 + 8x = -21 + 3x Solving -6 + 8x = -21 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -6 + 8x + -3x = -21 + 3x + -3x Combine like terms: 8x + -3x = 5x -6 + 5x = -21 + 3x + -3x Combine like terms: 3x + -3x = 0 -6 + 5x = -21 + 0 -6 + 5x = -21 Add '6' to each side of the equation. -6 + 6 + 5x = -21 + 6 Combine like terms: -6 + 6 = 0 0 + 5x = -21 + 6 5x = -21 + 6 Combine like terms: -21 + 6 = -15 5x = -15 Divide each side by '5'. x = -3 Simplifying x = -3
| 4t+10= | | 15x-30=6x+69 | | 7x+4=6x-4 | | -26=4(x+3)+2 | | 2(4x-1)+2=x+28 | | 15y+4=16 | | -49=4(3x-2)-5 | | 2(2x+3)=-x+1 | | -9x-19=-5x-43 | | -4=2(5x+3)+10 | | 3x+13=-6x+121 | | -18=3(x+2)+3 | | 10x+18=158 | | 2(5x+2)+1=-5 | | -21=3(4x+5) | | 5(3x+4)=5x+10 | | -35=5(3x-1) | | 2e-8f+6e+3f= | | 25=5(2x-5) | | 5(2x-5)=25 | | 3(5x-5)-9=36 | | 4(2x-5)+6=-46 | | 3(3x+2)=3x-36 | | -12=3(x+5) | | 3b-4a-(2b+a)= | | 5x+26=5(5x-3)+1 | | 6(1-2x)-3(x+1)= | | -x-6=7x-62 | | 7h-26=23 | | 4(2x+2)=-x-10 | | 4x+1=3(x-5)+5 | | 4=4(x+4) |